CXCL10 increases in human skeletal muscle following damage but is not necessary for muscle regeneration. Issue 8 (25th April 2018) - Deyhle, Michael R.; Hafen, Paul S.; Parmley, Jacob; Preece, Coray N.; Robison, Marissa; Sorensen, Jacob R.; Jackson, Blake; Eggett, Dennis L.; Hancock, Chad R.; Hyldahl, Robert D.
Abstract: CXCL10 is a chemokine for activated and memory T cells with many important immunological functions. We recently found that CXCL10 is upregulated in human muscle following contraction‐induced damage. No information is available on the role of CXCL10 in the context of muscle damage or repair. In this study, we confirm that CXCL10 is elevated in human muscle at 2 and 3 days following damage and perform cell culture and animal studies to examine the role of CXCL10 in muscle repair. CXCL10 did not impact proliferation rates of human primary myoblasts but it did promote myogenic differentiation in vitro, suggesting a possible direct impact on muscle regeneration. To test if CXCL10 was dispensable for effective muscle regeneration in vivo, we measured functional and histological markers of muscle repair out to 14 days postmuscle injury caused by a myotoxin in wild‐type (WT) mice and CXCL10 knockout (KO) mice. Between genotypes, no significant differences were found in loss or restoration of in situ muscle force, cross‐sectional area of newly formed myofibers, or the number of embryonic myosin heavy chain‐positive myofibers. In addition, KO animals were not deficient in T‐cell accumulation in the damaged muscle following injury. Gene expression of the other two ligands (CXCL9 and 11) that bind to the same receptor as CXCL10 were also elevated in the damaged muscle of KO mice. Thus, other ligands may have compensated for the lack of CXCL10 in the KO mice. We conclude that CXCL10 is not necessary for effective muscle regeneration. Abstract : This study was the first to investigate the role of the chemokine CXCL10 (also known as IP‐10) muscle regeneration following acute injury. CXCL10 was elevated in human muscle following contraction‐induced damage. However, CXCL10 knockout mice did not display any differences in muscle regeneration, restoration of functional capacity, or muscle T‐cell accumulation compared to the wild‐type animals.